Information modeling and relational databases - Halpin, T. A.; Morgan, Tony. (Burlington, MA : Morgan Kaufmann Publishers, 2008)
Information Modeling and Relational Databases, second edition, provides an introduction to ORM (Object-Role Modeling)and much more. In fact, it is the only book to go beyond introductory coverage and provide all of the in-depth instruction you need to transform knowledge from domain experts into a sound database design. This book is intended for anyone with a stake in the accuracy and efficacy of databases: systems analysts, information modelers, database designers and administrators, and programmers. Terry Halpin, a pioneer in the development of ORM, blends conceptual information with practical instruction that will let you begin using ORM effectively as soon as possible. Supported by examples, exercises, and useful background information, his step-by-step approach teaches you to develop a natural-language-based ORM model, and then, where needed, abstract ER and UML models from it. This book will quickly make you proficient in the modeling technique that is proving vital to the development of accurate and efficient databases that best meet real business objectives. *Presents the most indepth coverage of Object-Role Modeling available anywhere, including a thorough update of the book for ORM2, as well as UML2 and E-R (Entity-Relationship) modeling. *Includes clear coverage of relational database concepts, and the latest developments in SQL and XML, including a new chapter on the impact of XML on information modeling, exchange and transformation. * New and improved case studies and exercises are provided for many topics. * The book's associated web site provides answers to exercises, appendices, advanced SQL queries, and links to downloadable ORM tools.
Information levels and frameworks -- Conceptual modeling : first steps -- Uniqueness constraints -- Mandatory roles -- Value, set-comparison, and subtype constraints -- Other constraints and final checks -- Entity relationship modeling -- Data modeling in UML -- Advanced modeling issues -- Relational mapping -- Data manipulation with relational languages -- Using other database objects -- Schema transformations -- Process and state modeling -- Other modeling aspects and trends.
Includes bibliographical references (p. [913]-924) and index.
Keywords: Database design; Relational databases; Electronic books